Investigating students’ motivation and problems toward the use of Zoom platform in English teaching and learning process during the Covid-19 pandemic - Zuhratul Aini; Asnawi Muslem; Saiful Marhaban (Universitas Syiah Kuala, 2021)
This study was carried out to explore students’ motivation and problem toward the use of Zoom platform in teaching and learning English at Madrasah Aliyah Negeri (MAN) 1 Banda Aceh. The methods used in this research were quantitative and qualitative in nature. The instruments used were a set of questionnaire and interview. The data collected from the questionnaire were analyzed by using descriptive statistic in Microsoft Excel tool. Meanwhile, the data collected from the interview were analyzed by using words to describe the problem and solution because of teaching and learning through Zoom platform during Covid-19 pandemic. The result of this research found that the students relatively disagree with the use of Zoom platform in teaching and learning English. The percentage of students disagree was found 65% and the students’ agreement indication was found 35%. The dominant problem that faced by the students during teaching and learning using Zoom platform are related to the internet connection, misunderstanding material, nervousness, and eye strain. It can be resolved based on students’ solution related to the situations such as taking note and promoting a group discussion.